RETINAL FLUORESCEIN ANGIOGRAPHY IN SUSAC SYNDROME: A SHIFTING PATTERN OF ARTERIOLAR WALL HYPERFLUORESCENCE—A REPORT OF TWO CASES. Issue Volume 17:Issues 2(2023) (March 2023) - Van Oevelen, Kathy; Dirven, Werner; Tassignon, Marie-José; Van Os, Luc
Abstract : We present two cases of Susac syndrome, in which follow-up by means of retinal fluorescein angiography revealed a notable shifting pattern of arteriolar wall hyperfluorescence between subsequent angiographies, distal to the arteriolar wall hyperfluorescence of the previous fluorescein angiography. This phenomenon has not yet been reported in the literature. Abstract : Background: Susac syndrome consists of the triad of encephalopathy, branch retinal artery occlusion, and hearing loss and is believed to be an immune-mediated endotheliopathy. Arteriolar wall hyperfluorescence (AWH) on retinal fluorescein angiography (FA) has been described in the literature as a classic ophthalmic sign for Susac syndrome. In this article, we report a pattern of distally shifting segments of AWH on FA over time that was observed in two cases. Methods: Two cases of Susac syndrome are presented with an emphasis on FA findings, obtained at frequent intervals during follow-up. Results: In both cases, FA displays a shifting pattern of segments of AWH distal to the localization of the AWH observed on the previous FA. Conclusion: In patients with Susac syndrome, FA plays an important role in aiding diagnosis and monitoring the efficacy of treatment and disease activity during follow-up. In these two cases, the angiography revealed how the AWH can migrate along the vessel over time. This is the first published report showing an evolving distally shifting pattern of AWH in patients with Susac syndrome.